Temozolomide – Just a Radiosensitizer? - Kaina, Bernd; Beltzig, Lea; Strik, Herwig (Frontiers in Oncology, 2022)
Radiation concomitant with the DNA methylating drug temozolomide (TMZ) is the gold standard in the treatment of glioblastoma. In this adjuvant setting, TMZ is regarded to be a radiation sensitizer. However, similar to radiation, TMZ induces DNA double-strand breaks and is itself a potent trigger of apoptosis, cellular senescence and autophagy, suggesting that radiation and TMZ act independently. Although cell culture experiments yielded heterogeneous results, some data indicate that the cytotoxic effect of radiation was only enhanced when TMZ was given before radiation treatment. Based on the molecular mechanism of action of TMZ, the importance of specific TMZ and radiation-induced DNA lesions and their repair, as well as their interactions, possible scenarios for an additive or synergistic effect of TMZ with radiation are discussed, and suggestions for an optimal timing of radio-chemical treatments proposed.